Case Report: A giant but silent adrenal pheochromocytoma – a rare entity [version 1; referees: 2 approved] - Sunil Munakomi; Saroj Rajbanshi; Prof Shailesh Adhikary (F1000Research, 2016)
Herein we report a rare entity of a giant adrenal pheochromocytoma in a fifty-year-old male presenting with a vague abdominal pain. A computerised tomogram of the abdomen revealed a well-defined  left supraadrenal giant lesion with no evidence of invasion to surrounding structures.The patient underwent surgical excision without any untoward postoperative events. Histopathological study revealed a benign pheochromocytoma. This report highlights the importance of acknowledging the fact that sometimes a giant adrenal pheochromocytoma can present with paucity of clinical  signs and symptoms.Thorough investigations and a multidisciplinary team approach may lead  to a better outcome in these patients.